EKSISTENSI UPACARA KEAGAMAAN DI CANDI CETHO, KECAMATAN JENAWI, KABUPATEN KARANGANYAR - Purwanto, Heri; Titasari, Coleta Palupi (UHN IGB Sugriwa Denpasar, 2023)
Cetho Temple is one of the archaeological sites located on the western slope of Mount Lawu, has the status as a national level cultural heritage. Furthermore, its existence must be maintained and treated as well as possible. Currently the local community still uses Cetho Temple as place fot religious ceremony activities. This study reveals various types of religious ceremonies carried out in the Cetho Temple. The method used through observastions to the field, study of libraries, and the was analyzed. The results obtained tha local people still hold various ceremonies as a form of his contribution in maintaining and caring for Cetho Temple. The ceremony is Mondosio, Ruwahan, Dawuhan, Suran, Nyepi, Ngembak Geni, Galungan, Kuningan, Saraswati, Pagerwesi, Siwaratri, Panca Wali Krama, Nyadran, dan individual ceremony.